2016
DOI: 10.1002/ejsp.2215
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to tokenism: The role of individual characteristics in shaping responses to token decisions

Abstract: When only a handful of members from a disadvantaged group occupy positions of power, they are considered tokens. Previous research suggests that observers tend to consider tokenism as an egalitarian practice. Given its ambiguous nature, we hypothesized that reactions to tokenism would be shaped by individuals' sensitivity to inequality. In Study 1, we showed that women (vs. men) and individuals low (vs. high) on social dominance orientation differentiated more between a token and an egalitarian decision in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…First, the evidence in this study is consistent with resource dependence theory suggesting that firms benefit from corporate governance [18]. Second, the study highlights the legislative change to examine the differential effect of corporate governance on the value relevance of sustainability reports [9,46]. Lastly, we provided a natural experiment and event study to tease out any confounding effects on the results.…”
Section: Discussionsupporting
confidence: 73%
“…First, the evidence in this study is consistent with resource dependence theory suggesting that firms benefit from corporate governance [18]. Second, the study highlights the legislative change to examine the differential effect of corporate governance on the value relevance of sustainability reports [9,46]. Lastly, we provided a natural experiment and event study to tease out any confounding effects on the results.…”
Section: Discussionsupporting
confidence: 73%
“…A recent study showed, for example, that among women in the police force, experiencing a positive diversity climate only partially reduced the negative effects of underrepresentation, with the women continuing to show negative consequences of underrepresentation on identity conflict (Veldman et al, 2017). Other work has shown the dangers of piecemeal diversity initiatives and “token” minority representation (i.e., representation of only a few minority group members) that can blind people to existing inequality (Brady et al, 2015; Kirby et al, 2015; Anisman-Razin and Saguy, 2016; Gündemir and Galinsky, 2017), and should therefore not constitute the sole strategy to advance equality (see also Hentschel et al, 2013). Also, in generating a positive diversity climate, it is important that organizations also pay attention to the needs of the majority or high-status individuals, who similarly use information on diversity climate as an indicator of the degree to which their identity is accepted.…”
Section: Supportive Factors That Mitigate Threat or Its Effectsmentioning
confidence: 99%
“…Participant's feminist identification. We used two items (adapted from Anisman-Razin & Saguy, 2016) to assess participants' identification with feminism: "I identify with feminists" and "Being a feminist is a large part of my identity" (r = .78). We measured feminist identification after participants completed all other measures to avoid revealing the goal of the study.…”
Section: Methodsmentioning
confidence: 99%